การพัฒนาสูตรน้ำยาหล่อเย็นเพื่อแก้ปัญหาการเกิดสนิมภายในท่อสําหรับอุตสาหกรรมการผลิตท่อเหล็ก - พันธกานต์ นิ่มแสวงกุล (Chulalongkorn University, 2021)
Coolant is a type of synthetic chemical that can help lubricating a machine during operation. It can help reducing the heat generated by friction from the working machine and can prevent rust or reduce foaming. The main component in many machines is steel. Steel can be corroded and rusted over time, causing the decreasing in quality of the machine. This research studies the development of synthesized coolants to have ability to prevent and inhibit rust. In this study we choose 4 additives: monoethanolamine borate, monoethanolamide, morpholine and 2-aminoethanol. Rust testing was carried out using pure additive and mixture of 4 additives resulting in 15 formulations. The rust protection was tested according to the standard test method (IP287) at various concentrations of additives, 1% w/w, 0.5% w/w and 0.1% w/w, to determine the lowest concentration (break point) of each additive to prevent rusting. It was found that at a concentration of 0.5% w/w, there were 5 pure and mixed additives that caused the least rusting. Subsequently, these 5 pure and mixed additives were coated on two types of steel pipes: galvanized steel (white iron) and carbon steel (black iron). The coated iron tubes were then tested rust prevention by salt spray technique. Only black iron tubes can get rusted. Therefore, we choose the black iron tubes as samples to develop a new coolant formulation. It was found that only 2 types of mixed additives, monoethanolamide + morpholine and monoethanolamine borate + monoethanolamide + morpholine, gave the best rust prevention. Finally, rust protection by using cast black iron testing showed that only mixed additive of monoethanolamide + morpholine gave the best result. Then black iron tube coated with the best additive coolant was tested in salt spray test chamber. It was found that this coolant can prevent rust up to a period of 1 hour, which is equivalent to 7 days. However, when tested in the open air, this coolant can prevent rusting for only 3 days. Therefore, it can be concluded that our formula of anti-rust coolant can prevent rusting in about 3-7 days depending on usage and other factors.